ACCOUNTING IN THE WHARTON SCHOOL. - MacFarland, George A. (The Accounting Review, 1927)
The Wharton School of Finance and Commerce is the under-graduate school of business of the University of Pennsylvania in Philadelphia. After forty-five years of experience and development, the ideal set for the school by its dean, Emory R. Johnson, and the faculty, is to offer courses of study which will give to each student: first, a reasonably general education; second, a special training in the principles of business; and, third, opportunity to specialize in the field of business in which he is most interested. Where does accounting instruction belong in this three-part division of the curriculum? Certainly not in the first division with subjects such as English, history, political science, economics, sociology, and other studies of general educational value. Incidentally, these general studies are not concentrated in the first two years, but are taken concurrently with the technical subjects throughout the four years. Two accounting courses come in the second division of the curriculum, which division includes subjects offering a training in the principles of business in general, a training which must be considered a minimum vocational equipment for any business man.